Trends and predictions in the physical shape of Chinese preschool children from 2000 to 2020 - Tu, Chunjing; Pan, Qi; Jiang, Chongmin; Tu, Yuxuan; Zhang, Sanhua (Frontiers in Public Health, 2023)
Objective: To explore physical shape changes in preschool children from 2000 to 2020, and forecast development trends over the next 10 years. Method: Based on 247,088 preschool children's physical shape data obtained as time-series from five national physical fitness surveillance sessions in 31 provinces (autonomous regions and municipalities directly under the Central Government), a gray model GM (1,1) of their physical shape was constructed, and their growth and development levels in different periods were compared. Results: (1) During the period from 2000 to 2020, the height, weight and chest circumference of Chinese preschool children all increased rapidly. Specifically, the weight of male and female children increased by 1.8 kg and 1.6 kg, their chest circumference increased by 1.6 cm and 1.5 cm, respectively, and both their heights increased by 3.6 cm. Among these indicators, the older the age, the greater the growth rate. It is expected that all the indicators will continue to grow rapidly over the next 10 years, but the growth rate will slow. (2) From 2000 to 2020, the growth rate of weight was higher than that of height, and BMI showed an increasing trend. The obesity detection rates in boys and girls increased by 5.6% and 2.8%, respectively. Over the next ten years, the incidence of obesity is expected to increase by 3.8% in boys and 2.8% in girls. (3) Improvement in the growth and development of preschool children in China has a certain correlation with the rapid growth of China's economy, less physical activity, education and other factors. Conclusion: Over the past 20 years, the growth and nutritional status of Chinese preschoolers have improved dramatically, but overweight and obesity remain. Overweight and obesity rates are expected to continue to increase rapidly over the next ten years, particularly among boys, and effective measures should be taken to control the obesity epidemic.